"Sister Chromatid Exchanges and Micronuclei in Lymphocyte of Nurses Handling Antineoplastic Drugs" - M Ansari-Lari; M Saadat; M Shahryari; DD Farhud (Tehran University of Medical Sciences, 2001)
Individuals handling antineoplastic drugs or their wastes may absorb these potent genotoxic agents. The effects of handling antineoplastic drugs were examined in a group of 24 nurses working in the hematology and oncology departments of two different university hospitals in Shiraz (Iran) and in a group of 18 unexposed nurses as control group. The cytogenetic repercussions of exposure were assessed by examining sister chromatid exchanges (SCEs) and micronuclei (Mn) in circulating lymphocytes. A significant increased frequencies of SCE and Mn is observed in circulating lymphocytes. A significant increased frequencies of SCE and Mn is observed in nurses in daily contact with antineoplastic drugs as compared to control group.